Experiment in supra-national governance : the Caribbean Regional Negotiating Machinery - Grant, Cedric ([s.n.] [S.l.], 1999)
Attempts to focus on the creation of a supranational institution within a regional grouping of developing countries engaged in efforts to deepen its integation process. Examines the Caribbean Common Market and Community's (CARICOM) experiment in the regional governance of the negotiations between its member states and their trading partners and of those in the World Trade Organization (WTO). Discusses the main factors at work in the establishment and elaboration of the Regional Negotiating machinery (RNM). Pays attention to the process of regional policy formation and the relationship between the RNM and the other key actors in the negotiating process, the Caribbean Community Secretariat and the member states. Discusses the performance of the RNM.